Effects of soaked hay on lung function and airway inflammation in horses with severe asthma - Roxane Westerfeld; Flavie Payette; Valérie Dubuc; Estelle Manguin; Khristine Picotte; Guy Beauchamp; Christian Bédard; Mathilde Leclere (Journal of Veterinary Internal Medicine, 2024)
Abstract Background Reducing inhaled dust particles improves lung function in horses with severe asthma. Soaked hay is commonly used by owners, but its efficacy in improving lung function and inflammation has not been documented. Objectives To measure the effects of soaked hay and alfalfa pellets in horses with severe asthma. Animals Ten adult horses with severe asthma from a research colony. Methods Prospective controlled trial. Horses in clinical exacerbation were housed indoors and allocated to be fed either soaked hay (n = 5) or alfalfa pellets (n = 5) for 6 weeks. Soaked hay was immersed for 45 minutes and dried out hay was discarded between meals. Pulmonary function and clinical scores were measured before and after 2, 4, and 6 weeks. Tracheal mucus scores and bronchoalveolar lavages were performed before and after 6 weeks. Lung function was analyzed with a linear mixed model using log‐transformed data. Results Lung resistance decreased from (median (range)) 2.47 (1.54‐3.95) to 1.59 (0.52‐2.10) cmH2O/L/s in the pellets group and from 1.89 (1.2‐3.54) to 0.61 (0.42‐2.08) cmH2O/L/s in the soaked hay group over the 6‐week period for an average difference of 1.06 cmH2O/L/s for pellets (95% confidence interval [95% CI]: 0.09‐2.04, P = .03, not significant after correction) and 1.31 cmH2O/L/s for soaked hay (95% CI: −0.23 to 2.85, P < .001, significant). Conclusion and Clinical Importance Soaked hay can control airway obstruction in horses with severe asthma. The strict protocol for soaking and discarding dried‐out hay in this study could however be considered too great of an inconvenience by owners.